Patient-derived xenograft (PDX) models, applications and challenges in cancer research - Abdolahi, Shahrokh; Ghazvinian, Zeinab; Muhammadnejad, Samad; Saleh, Mahshid; Asadzadeh Aghdaei, Hamid; Baghaei, Kaveh (Journal of translational medicine, 2022)
The establishing of the first cancer models created a new perspective on the identification and evaluation of new anti-cancer therapies in preclinical studies. Patient-derived xenograft models are created by tumor tissue engraftment. These models accurately represent the biology and heterogeneity of different cancers and recapitulate tumor microenvironment. These features have made it a reliable model along with the development of humanized models. Therefore, they are used in many studies, such as the development of anti-cancer drugs, co-clinical trials, personalized medicine, immunotherapy, and PDX biobanks. This review summarizes patient-derived xenograft models development procedures, drug development applications in various cancers, challenges and limitations.